Expressions of love and sexual union in Hesiod’s Catalogue of Women - Aguirre Castro, Mercedes (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2005)
In the Catalogue of Womenthe sexual union of the heroines with the gods and heroes is conveyed by various formulaic expressions which allude to a human wedding or to nuptial bed, or by some other expressions which refer to love in different ways. The aim of this article is to examine the use that the poet makes of those formulaic expressions, the alternation between them, and his preferences. Furthermore, this study aims to compare the expressions describing love and sexual union in the fragments referring to the offspring of several mortal women with the last passage of the Theogony –or even with all of the Theogony–, trying to find similarities or differences which might allow us to relate both poems.
Keywords: Hesiod; Catalogue of Women; formulae; love; sexual union; wedding; heroines